Desarrollo de aplicación móvil para el registro y seguimiento de equipos biomédicos en la Clínica Colsubsidio Calle 100 por medio de Internet de las cosas - Santafé Alfonso, Mónica Andrea (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
The Internet of Things (IoT) consists of the interconnection of everyday objects through the combination of devices and their connection with Internet protocols. In health, the IoT has been used in the monitoring of health parameters in patients, in document and endowment management, and in the supervision of drugs, samples, equipment maintenance and patient well-being. The movement of medical equipment between services and rooms in the institution is recurrent, and the registration of these movements is not usual, so there are problems in locating a biomedical team. For this reason, this document presents the development of a mobile application through IoT, which allows the control and management of the information of biomedical equipment with greater frequency of movement in the Colsubsidio Calle 100 Clinic. The mobile application " Serial App ” was designed and developed for managing the inventory of biomedical equipment, registration of vital information and the current and assigned location. Vital signs monitors, multiparameter monitors, infusion pumps and mechanical ventilators were included in the database created. Based on the results of the user experience and usability tests, the positive impact of the application on users was verified and suggestions and comments were received to improve the functionality of the project in the future.

El Internet de las cosas (IoT) consiste en la interconexión de objetos de la vida cotidiana mediante la combinación de dispositivos y su conexión con protocolos de internet. En la salud, el IoT ha sido utilizado en el monitoreo de parámetros de la salud en pacientes, en la gestión documental y dotacional, y en la supervisión de fármacos, muestras, mantenimiento de equipos y el bienestar del paciente. El desplazamiento de los equipos médicos entre servicios y habitaciones en la institución es recurrente, y el registro de estos movimientos no es usual, por lo que hay inconvenientes para localizar un equipo biomédico. Por tal razón, el presente documento presenta el desarrollo de una aplicación móvil a través de IoT, que permite el control y gestión de la información de equipos biomédicos con mayor frecuencia de traslado en Clínica Colsubsidio Calle 100. Se diseñó y desarrolló la aplicación móvil “Serial App” para la gestión del inventario de equipos biomédicos, registro de la información vital y de la localización actual y asignada. En la base de datos creada se incluyeron monitores de signos vitales, monitores multiparámetros, bombas de infusión y ventiladores mecánicos. A partir de los resultados de las pruebas de experiencia de usuario y usabilidad, se comprobó el impacto positivo de la aplicación en los usuarios y se acogieron las sugerencias y comentarios para mejorar la funcionalidad del proyecto en un futuro.
Keywords: Aplicación móvil; Equipo biomédico; Escáner; Inventario; Internet de las cosas; Mobile App; Biomedical equipment; Scanner; Inventory; Internet of things